MICROBIAL ANALYSIS OF NUNDKOL LAKE WATER - Sharma, Meenakshi; Mishra, Manjul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the water quality of Nundkol Lake, also known as Nandi Kund or Kalodaka Lake, located in the Ganderbal district of the Kashmir Valley, Jammu and Kashmir, India. Conducted over a year (January to December 2023), the research aimed to assess the lake’s physicochemical properties and their ecological implications. Surface water samples were collected using clean glass stoppered bottles, adhering to the guidelines established by the American Public Health Association (APHA, 2005). Various limnological parameters were analyzed, including temperature, pH, specific conductivity, Secchi transparency, dissolved oxygen, free CO2, alkalinity, phosphate (PO4-P), and nitrate (NO3-N). Measurements were taken on-site, with select samples transported under ideal conditions to a laboratory for detailed analysis. The findings highlighted a significant correlation between physicochemical parameters and the lake’s ecological health. Nundkol Lake, situated at an elevation of 5,142 meters (16,870 feet) above sea level, is fed by glacial runoff from Gangabal Lake and Mount Haramukh and features a diverse array of alpine flora and brown trout. Access to the lake is limited to summer months due to heavy snowfall in winter. This research emphasizes the importance of ongoing water quality monitoring in Nundkol Lake to ensure its ecological sustainability and to better understand its response to environmental stressors. The study contributes valuable data for the conservation and management of high-altitude freshwater ecosystems in the region.